2023
DOI: 10.1186/s40066-022-00398-x
|View full text |Cite
|
Sign up to set email alerts
|

Are sub-Saharan African national food and agriculture policies nutrition-sensitive? A case study of Ethiopia, Ghana, Malawi, Nigeria, and South Africa

Abstract: Background In sub-Saharan Africa (SSA), malnutrition coupled with rising rates of undernutrition and the burden of overweight/obesity remains one of the most significant public health challenges facing the region. Nutrition-sensitive agriculture can play an important role in reducing malnutrition by addressing the underlying causes of nutrition outcomes. Therefore, we aim to assess the nutrition-sensitivity of food and agriculture policies in SSA and to provide recommendations for identified po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…48 Still, the decrease in budgetary allocations to the Nutrition Division from 2018 to 2020 is of particular concern because it might be due to inadequate spending by the Nutrition Division in 2017. Several authors have highlighted that implementation of the AFSNS has been inadequate, [49][50][51] not just because of inadequate funding, but because of insufficient capacities to implement. 49 Nigeria used incremental budgeting in preparing budgets up until 2016.…”
Section: Discussionmentioning
confidence: 99%
“…48 Still, the decrease in budgetary allocations to the Nutrition Division from 2018 to 2020 is of particular concern because it might be due to inadequate spending by the Nutrition Division in 2017. Several authors have highlighted that implementation of the AFSNS has been inadequate, [49][50][51] not just because of inadequate funding, but because of insufficient capacities to implement. 49 Nigeria used incremental budgeting in preparing budgets up until 2016.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with a recent study conducted in Rwanda on local manufacturing of generics products, which reported the limited manufacturing capacity as one of the challenges to the availability of health products (26). Different studies conducted in Sub-Saharan Africa reported limited local production capacity of nutrition products to cause long lead time of manufacturers and suppliers (22,(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…While the AFSNS has been reported to be a comprehensive strategy, it has remained largely unimplemented 7 years after its ratification. 18 Ensuring that the available capacity can cope in the short term with the scope of NSA activities planned is important.…”
Section: Lessons From Nigeria’s Experiencesmentioning
confidence: 99%
“…Agricultural policies prior to 2010 did not explicitly address nutrition and included limited considerations for food security. 18,20,21 Beginning from the National Agricultural Investment Plan (NAIP) 2011-2014 developed in 2010, influenced by the Comprehensive African Agriculture Development Programme (CAADP), 22 and drawing on experiences from a nutrition-sensitive National Programme on Food Security that commenced in 2008, agricultural policies and strategies in Nigeria began to include nutrition objectives, activities, and/ or indicators, 23 leading to intentional implementation of NSA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation